Ecology Of Mosquitoes From Kolhapur District, India - T. V. SATHE, (International Journal of Pharma and Bio Sciences, 2011)
Kolhapur district of Maharashtra, India contains several small and large water bodies as natural and artificial breeding places for mosquitoes. The distribution of various mosquito genera in natural and artificial habitats and their relative species abundance was studied during the years 2009-2011. In all, 22 mosquito species belonging to three genera viz. Anopheles, Culex and Aedes, which were potential vectors of malaria, dengue, chikungunia, filaria and Japanese encephalitis of human in the district were surveyed. A total of 2113 mosquito larvae were collected from artificial sources and 1993 larvae were harvested from natural sources. Anopheles (Cellia) culicifacies Giles, Culex (Culex) fatigans Widemam, Aedes (Stegomyia) aegypti Linnaeus and Ae (S.) albopictus Skuso were dominant over other species. Favorable environmental conditions for breeding mosquitoes and impact of human activities on population dynamics of mosquitoes have also been studied.